The Declining Competitiveness of French Firms Reflects a Generalised Supply-Side Problem - Boulhol, Hervé (OECD Publishing, 2014)
This short paper analyses the decline of France's trade balance over the past 15 years. While the loss in export market shares is comparable to that of the major OECD countries except Germany, it is one of the largest among the countries of the euro area. The determinants of this outcome seem to be general (rather than concentrated in the industrial sector) and related to overall supply-side weaknesses
Keywords: Employment; Economics; Industry and Services; France